Ensino de eletricidade e magnetismo orientado por projetos de pesquisa com sucata eletrônica - Andrade, Francisco Andreázio Lôbo de (Universidade Federal Rural do Semi-Árido, 2018)
This dissertation presents the planning, elaboration and testing of an educational product entitled Teaching Electricity and Magnetism Oriented by Research Projects with Electronic Waste. The didactic intervention includes a semester of conventional classes supported in the textbook adopted in the school; investigation of misconceptions about simple electrical circuits, and the use of a didactic sequence similar to potentially meaningful teaching units (PMTU). During the second semester the class was divided into five groups, three of which were in charge of building a Tesla coil, and the other two built a metal detector. These equipments were constructed with components extracted by the own students, of computers that were out of use in the school. It was evident the pleasure that the students had in disassembling the computers and in assembling the equipments. Although at the end of the didactic intervention the students showed reasonable declarative knowledge, in the Ausubelian sense, many of them continued to present the misconceptions exhibited during the pre-test. This result is similar to many reported in the literature, accounting for the strong persistence of some misconceptions
Keywords: Ensino de física; Eletricidade; Magnetismo; Ensino orientado por projetos; Sucata eletrônica; Physics teaching; Electricity; Magnetism; Oriented project teaching; Electronic waste; CIENCIAS EXATAS E DA TERRA::FISICA